Disturbed natural killer cell homeostasis in the salivary gland enhances autoimmune pathology via IFN-γ in a mouse model of primary Sjögren’s syndrome - Sato, Mami; Arakaki, Rieko; Tawara, Hiroaki; Nagao, Ruka; Tanaka, Hidetaka; Tamura, Kai; Kawahito, Yuhki; Otsuka, Kunihiro; Ushio, Aya; Tsunematsu, Takaaki; Ishimaru, Naozumi (Frontiers in Medicine, 2022)
Objective: Innate lymphoid cells (ILCs), including natural killer (NK), ILC1, ILC2, lymphoid tissue-inducer (LTi) cells, and ILC3 cell, play a key role in various immune responses. Primary Sjögren’s syndrome (pSS) is an autoimmune disease characterized by chronic inflammation of exocrine glands, such as the lacrimal and salivary glands (SGs). The role of NK cells among ILCs in the pathogenesis of pSS is still unclear. In this study, the characteristics and subsets of NK cells in the salivary gland (SG) tissue were analyzed using a murine model of pSS. Methods: Multiple phenotypes and cytotoxic signature of the SG NK cells in control and pSS model mice were evaluated by flow cytometric analysis. Intracellular expression of interferon-γ (IFN-γ) among T cells and NK cells from the SG tissues was compared by in vitro experiments. In addition, pathological analysis was performed using anti-asialo-GM1 (ASGM1) antibody (Ab)-injected pSS model mice. Results: The number of conventional NK (cNK) cells in the SG of pSS model mice significantly increased compared with that in control mice at 6 weeks of age. The production level of IFN-γ was significantly higher in SG NK cells than in SG T cells. The depletion of NK cells by ASGM1 Ab altered the ratio of tissue resident NK (rNK) cells to cNK cells, which inhibited the injury to SG cells with the recovery of saliva secretion in pSS model mice. Conclusion: The results indicate that SG cNK cells may enhance the autoreactive response in the target organ by upregulating of IFN-γ, whereas SG rNK cells protect target cells against T cell cytotoxicity. Therefore, the activation process and multiple functions of NK cells in the target organ could be helpful to develop potential markers for determining autoimmune disease activity and target molecules for incurable immune disorders.